2013
DOI: 10.1590/s0004-28032013000400002
|View full text |Cite
|
Sign up to set email alerts
|

Tomographic Findings of Gastric Gastrointestinal Stromal Tumor and Correlation With the Mitotic Index

Abstract: -Context -Gastrointestinal stromal tumors are uncommon abdominal neoplasms and can affect any portion of the gastrointestinal tract. Objectives -Describe the tomographic findings of the gastrointestinal stromal tumor of gastric origin, correlating it with the mitotic index. Methods -Twenty-one patients were selected within the period of January 2000 and 2008, with histopathological and immunohistochemical diagnosis of gastric gastrointestinal stromal tumors, who presented computed tomography done before the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…In a study of O'Neill et al (21) , which assessed the metastatic risk of gastric GISTs by CT features according to the AFIP criteria, they found that tumor size >10 cm, an irregular/lobulated margin and the presence of a solid enhancing component were independently associated with an increased risk of metastatic disease, a higher mitotic count and worse survival. Similar to our study, Pelandre et al (12) . included only gastric GISTs in their study, and found a statistically significant correlation between irregular morphology, mesenteric heterogeneity and high mitotic index.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In a study of O'Neill et al (21) , which assessed the metastatic risk of gastric GISTs by CT features according to the AFIP criteria, they found that tumor size >10 cm, an irregular/lobulated margin and the presence of a solid enhancing component were independently associated with an increased risk of metastatic disease, a higher mitotic count and worse survival. Similar to our study, Pelandre et al (12) . included only gastric GISTs in their study, and found a statistically significant correlation between irregular morphology, mesenteric heterogeneity and high mitotic index.…”
Section: Discussionsupporting
confidence: 93%
“…GISTs occur at a median age of 60 years in most series (8,12,16,17) . In our study, GISTs have no gender predilection like some other studies (5,13,15) ; however, a male predominance has been shown in the literature (18,19) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mitotic count of a GIST could be used as a prediction target. Several studies have demonstrated the applicability and clinical value of the mitotic count (27,28).…”
Section: Discussionmentioning
confidence: 99%